2021
DOI: 10.1093/rheumatology/keab953
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of belimumab during maintenance therapy in patients with systemic lupus erythematosus

Abstract: Objectives The efficacy of belimumab (BEL) during maintenance therapy in patients with systemic lupus erythematosus (SLE) remains unclear in the real-life clinical setting. This study investigated the efficacy and safety of BEL in patients with SLE during maintenance therapy. Methods In this retrospective observational study, maintenance therapy was defined as low-dose glucocorticoid (GC) therapy (prednisolone equivalent dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Notably, no discontinuation due to a lack of e cacy was observed in both groups, suggesting that BLM may have characteristics similar to HCQ. The current ndings indicate that BLM has a high safety pro le, as noted in a previous study [18,19,32]. While similar comparisons need to be made for immunosuppressive agents and other biologic agents, at this stage, BLM seems the most reasonable treatment alternative for patients who cannot tolerate HCQ because of adverse effects or concerns about cumulative dosage.…”
Section: Discussionsupporting
confidence: 75%
“…Notably, no discontinuation due to a lack of e cacy was observed in both groups, suggesting that BLM may have characteristics similar to HCQ. The current ndings indicate that BLM has a high safety pro le, as noted in a previous study [18,19,32]. While similar comparisons need to be made for immunosuppressive agents and other biologic agents, at this stage, BLM seems the most reasonable treatment alternative for patients who cannot tolerate HCQ because of adverse effects or concerns about cumulative dosage.…”
Section: Discussionsupporting
confidence: 75%
“…One recent study in patients with SLE, of which just under half had LN class I–V, reported that belimumab, in combination with ST, during maintenance therapy significantly reduced corticosteroid dose and prevented relapse of LN when compared with ST, in a real-world clinical setting. 60 …”
Section: Discussionmentioning
confidence: 99%
“…One recent study in patients with SLE, of which just under half had LN class I-V, reported that belimumab, in combination with ST, during maintenance therapy significantly reduced corticosteroid dose and prevented relapse of LN when compared with ST, in a real-world clinical setting. 60 There remains a knowledge gap on whether belimumab is superior to ST for maintaining the response achieved during induction therapy and preventing renal flares, which is an important goal of maintenance therapy in LN. 8 To address this, the MOONLIGHT study will evaluate the real-world clinical effectiveness of belimumab in combination with ST in Japanese patients with a history of biopsy-diagnosed active LN using real-world clinical data from a nationwide surveillance study and a multicentre registry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Another study also reported that the addition of belimumab to standard-of-care treatment was effective in reducing glucocorticoids, preventing relapse of disease activity and preventing the progression of organ damage in patients with SLE during maintenance therapy after obtaining remission or low disease activity. 31 These findings may be important aspects in the treat-to-target context during maintenance therapy for SLE.…”
Section: Belimumab Therapy In Systemic Lupus Erythematosusmentioning
confidence: 93%